When and How-Long: A Unified Approach for Time Perception - Maniadakis, Michail; Trahanias, Panos (Frontiers in Psychology, 2016)
The representation of the environment assumes the encoding of four basic dimensions in the brain, that is the 3D space and time. The vital role of time for cognition is a topic that recently attracted gradually increasing research interest. Surprisingly, the scientific community investigating mind-time interactions has mainly focused on interval timing, paying less attention on the encoding and processing of distant moments. The present work highlights two basic capacities that are necessary for developing temporal cognition in artificial systems. In particular, the seamless integration of agents in the environment assumes they are able to consider when events have occurred and how long they have lasted. This information, although rather standard in humans, is largely missing from artificial cognitive systems. In the present work we consider how a time perception model that is based on neural networks and the Streatal Beat Frequency (SBF) theory is extended in a way that besides the duration of events, facilitates the encoding of the time of occurrence in memory. The extended model is capable to support skills assumed in temporal cognition and answer time-related questions about the unfolded events.